The effect of different environmental conditions on visual merit of turf grasses. - Prończuk, Sławomir; Żurek, Grzegorz (Plant Breeding and Seed Science, 2008)
Three different types of environmental conditions were used in five years of turf grass evaluation: no.1 – in sun, moderately intensive management with irrigation; no.2 – in park shade, extensively managed but irrigated when necessary; no.3 – in park shade, extensively managed and not irrigated. Visual merit (VM) of following cultivars was scored in 1 – 9 scale: perennial ryegrass Stadion, red fescue Nimba, smooth-stalked meadow grass Conni, tall fescue Asterix, prostrate meadow grass Supranova and tufted hairgrass Brok...